SMALL SIGNAL ANALYSIS OF LOAD ANGLE GOVERNING AND EXCITATION CONTROL OF AC GENERATORS (Nigerian Journal of Technology, 2005)
A method of obtaining direct pictorial information on the behaviour of synchronous machines under different conditions of control using a single variable related to its load angle is presented. The technique employs a simple control scheme to the linearized model of synchronous machine equations. The scheme is simple and can be manipulated on a PC if adequate computational data is provided. Simulation results obtained using MATLAB ® were revealed by angle-time plots. These results are very similar to results obtained by frequency response analysis. Results of other related schemes modeled with laboratory micro-machines also attest to the validity of this technique. Four control modes were simulated and it is shown that in all but one, there is a remarkable improvement in system damping than all the conventional schemes considered in the study. More significantly, responses of the new scheme display a better performance in terms of speed of response, control co-ordination and simplicity than the well-known techniques of employing power system stabilizers (PSS) or using terminal voltage for control of exciter and speed signal for governor. Above all, there is no need for supplementary signals that could further complicate the proposed control loop.